Echo time-dependence of observed lung T1 in patients with cystic fibrosis and correlation with clinical metrics - Triphan, Simon M. F.; Stahl, Mirjam; Jobst, Bertram; Sommerburg, Olaf; Kauczor, Hans-Ulrich; Schenk, Jens-Peter; Alrajab, Abdulsattar; Eichinger, Monika; Mall, Marcus A.; Wielpütz, Mark Oliver (Journal of magnetic resonance imaging, 2020)
Background Noninvasive monitoring of early abnormalities and therapeutic intervention in cystic fibrosis (CF) lung disease using MRI is important. Lung T1 mapping has shown potential for local functional imaging without contrast material. Recently, it was discovered that observed lung T1 depends on the measurement echo time (TE). Purpose To examine TE-dependence of observed T1 in patients with CF and its correlation with clinical metrics. Study Type Prospective. Population In all, 75 pediatric patients with CF (8.6 ± 6.1 years, range 0.1-23 years), with 32 reexamined after 1 year. Field Strength/Sequence Patients were examined at 1.5T using an established MRI protocol and a multiecho inversion recovery 2D ultrashort echo time (UTE) sequence for T1(TE) mapping at five TEs including TE1 = 70 μs. Assessment Morphological and perfusion MRI were assessed by a radiologist (M.W.) with 11 years of experience using an established CF-MRI scoring system. T1(TE) was quantified automatically. Clinical data including spirometry (FEV1pred%) and lung clearance index (LCI) were collected. Statistical Tests T1(TE) was correlated with the CF-MRI score, clinical data, and LCI. Results T1(TE) showed a different curvature in CF than in healthy adults: T1 at TE1 was shorter in CF (1157 ms ± 73 ms vs. 1047 ms ± 70 ms, P < 0.001), but longer at TE3 (1214 ms ± 72 ms vs. 1314 ms ± 68 ms, P < 0.001) and later TEs. The correlations of T1(TE) with patient age (ρTE1-TE5 = −0.55, −0.44, −0.24, −0.30, −0.22), and LCI (ρTE1-TE5 = −0.43, −0.42, −0.33, 0.27, −0.22) were moderate at ultra-short to short TE (P < 0.001) but decreased for longer TE. Moderate but similar correlations at all TE were found with MRI perfusion score (ρTE1-TE5 = −0.43, −0.51, −0.47, −0.46, −0.44) and FEV1pred% (ρTE1-TE5 = +0.44, +0.44, +0.43, +0.40, +0.39) (P < 0.05). Data Conclusion TE should be considered when measuring lung T1, since observed differences between CF and healthy subjects strongly depend on TE. The different variation of correlation coefficients with TE for structural vs. functional metrics implies that TE-dependence holds additional information which may help to discern effects of tissue structural abnormalities and abnormal perfusion. Level of Evidence 2 Technical Efficacy Stage 1 J. MAGN. RESON. IMAGING 2020;52:1645-1654.